Injury-feigning in the Anatidae - Hebard, Frederick V (Wildfowl, 1960)
Injury-feigning or some apparently allied form of distraction behaviour performed by parents caring for broods when confronted by a predator has been recorded in at least 58 species of the family Anatidae. But it seems not to occur in a few species and there are many others whose parental behaviour is undescribed. The purpose of this paper is to summarize what is now known in the hope of stimulating further observations and to draw attention to the possible taxonomic value of the presence or absence of such behavior.